Dictionary of nursing theory and research - Powers, Bethel Ann, 1943- (Springer Pub. Co., 2006)
An essential reference, particularly for students who encounter nursing theory and research courses in their educational programs ... In her foreword ... Afaf Meleis states that it is the answer to a graduate student's prayers. I would certainly agree, and I would add that experienced researchers and theoreticians can use it as a handy reference for day-to-day scholarly activities."--Nursing Education Perspectives. Updated terminology and the addition of many new terms with examples and references that reflect current nursing practice make this third edition of the Dictionary of Nursing The